2017
DOI: 10.3390/ijerph14030263
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Epidemiology of Human Fatal Infections with Novel, High (H5N6 and H5N1) and Low (H7N9 and H9N2) Pathogenicity Avian Influenza A Viruses

Abstract: This study aimed to assess the mortality risks for human infection with high (HPAI) and low (LPAI) pathogenicity avian influenza viruses. The HPAI case fatality rate (CFR) was far higher than the LPAI CFR [66.0% (293/444) vs. 68.75% (11/16) vs. 40.4% (265/656) vs. 0.0% (0/18) in the cases with H5N1, H5N6, H7N9, and H9N2 viruses, respectively; p < 0.001]. Similarly, the CFR of the index cases was greater than the secondary cases with H5N1 [100% (43/43) vs. 43.3% (42/97), p < 0.001]. Old age [22.5 vs. 17 years f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 44 publications
1
44
0
Order By: Relevance
“…Information obtained from relations has been reported to be major source of information about avian influenza in Chinese communities (Voeten et al, 2009). Although zoonotic HPAI H5N1 has occurred in some countries, with variable case fatalities (Fasina et al, 2010;Wu et al, 2017), our study found some traders to be unaware of HPAI H5N1 to be zoonotic. This could be because infection in humans at LBMs has not been reported in Nigeria (Fasina et al, 2009), till date.…”
Section: Discussionmentioning
confidence: 56%
“…Information obtained from relations has been reported to be major source of information about avian influenza in Chinese communities (Voeten et al, 2009). Although zoonotic HPAI H5N1 has occurred in some countries, with variable case fatalities (Fasina et al, 2010;Wu et al, 2017), our study found some traders to be unaware of HPAI H5N1 to be zoonotic. This could be because infection in humans at LBMs has not been reported in Nigeria (Fasina et al, 2009), till date.…”
Section: Discussionmentioning
confidence: 56%
“…Human infection with H5N6 virus manifests as flulike symptoms such as fever and cough in the early stage, but rapidly progresses to severe pneumonia (10,11). The fatality rate of human infection with H5N6 avian influenza virus is higher than that of low pathogenic avian influenza virus (H7N9 and H9N2) (12) and seasonal influenza virus (subtype H1N1, H3N2, and B) (13)(14)(15). Treatment with oseltamivir within 48 hours of illness onset can effectively reduce the severity and mortality caused by avian influenza virus infection (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, novel reassortant avian influenza virus strains are constantly emerging (28,29), which will endanger human health and cause great economic losses. Several types of avian influenza virus (H5N1, H5N6, H7N9, H7N4, H6N1, H9N2, and H10N8) have been confirmed to cause severe human infections in China (12,(30)(31)(32). In order to effectively respond to potential influenza pandemics, surveillance of viral mutations should be strengthened, especially mutations that may enhance drug resistance and transmission capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Our model assumptions are valid for the avian influenza virus because it is mainly transmitted through direct contact with infected hosts or their secretions and infection does not confer longlasting immunity (Stallknecht et al, 1990;Alexander, 2000;2007). The avian influenza virus induces symptoms such as lethargy, depression and anorexia prior to death in infected hosts, and the different virus strains are often classified as low pathogenic (LPAI) and highly pathogenic (HPAI) strains based on the severity of lethargy and the case fatality rate/ratio they cause in birds (Perkins & Swayne, 2001;Mutinelli et al, 2003;Bertran et al, 2011;Belser et al, 2013;Wu et al, 2017). Infected chickens may have more contacts before lethargy because they are more active in the chicken pen or more likely to be transported between locations.…”
Section: Discussionmentioning
confidence: 99%